INVESTIGATING EFFECTS OF STRATEGICINTELLIGENCE OF MANAGERS ON THE PERFORMANCE OF EMPLOYEES (CASE STUDY: PRIVATE BANKS IN BAGHDAD PROVINCE) - Firas Salman Khudhair; Rafiduraida Abdul Rahman; Ahmad Amri Bin Zainal Adnan; Dr. Anmar Adnan Khudhair (European Journal of Research Development and Sustainability, 2022)
This study examines the impact of strategic intelligence of executive managers on the performance of employees in private banks of Baghdad. The research method is descriptive and correlational. The population of this study is consisted of all the employees of private banks in Baghdad, which is according to the latest data, a number of 450 individuals. Using simple stratified sampling method and Cochran’s formula, 216 subjects were selected as final samples to be studied. In order to measure the variables used in this research, two questionnaires of "the Strategic Intelligence" and " Performance-Evaluation of Employees" were used. Validity of the abovementioned questionnaires were confirmed by experts and their reliability were measured using Cronbach’s alpha coefficient that was respectively 0.82 for Strategic Intelligence and 0.84 for employees’ performance. Also, Statistical methods were used for the analysis of final descriptive and inferential statistics (methods like one-variable regression, stepwise regression and structural equation modeling). The results showed that strategic intelligence and all its dimensions – i.e. competitive intelligence, business intelligence and knowledge management- have great impacts on employees’ organizational performance. Stepwise regression analysis showed that all three aspects of strategic intelligence have the ability to predict the performance of their employees. Finally, structural equation modeling showed that the causal impact of strategic intelligence on employees’ performance has a satisfactory level of appropriateness